PARTISIPASI POLITIK MASYARAKAT DALAM MEMPERTAHANKAN DESA MANDIRI (Studi Desa Sambonggede Kecamatan Merakurak Kabupaten Tuban) - Mangihut Siregar (Universitas Wijaya Kusuma Surabaya, 2023)
Community participation plays an important role in every program launched by the government. Community participation can be carried out in groups or individually. Through participation, the interests of society will be accommodated. This research was conducted using a qualitative descriptive method by collecting data by observation, interviews and documents. The results of the study show that community participation carried out in Sambonggede Village, Merakurak District in maintaining an independent village has a very important role. Community participation that has been carried out by groups and individuals through participation in decision making, participation in the implementation of activities, participation in development monitoring and evaluation, and participation in the utilization of development results.Keywords: Political participation, community participation, independent village.